A Class of Best-Response Potential Games - Davide Dragone; Luca Lambertini; Arsen Palestini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
We identify a class of noncooperative games in continuous strategies which are best-response potential games. We identify the conditions for the existence of a best-response potential function and characterize its construction, describing then the key properties of the equilibrium. The theoretical analysis is accompanied by applications to oligopoly and monetary policy games.
Keywords: 330